Effect of Phenological Basis Deficit Irrigation on Yield and Water Use Efficiency of Tomato (Solanum lycopersicon L.) - Gebreigziabher, Ekubay Tesfay; Assefa, Netsanet Fissha (Food, Agriculture and Natural Resources - NETWORKS, 2024)
The availability of water is a major concern in regions with limited water resources. In such regions, the focus of irrigation management shifted from producing per unit area to producing per unit of water consumed, water productivity. An experiment was carried out, for two consecutive years( 2020 and 2021) at the research farm of Shire-Maitsebri Agricultural Research Center, Tselemty district, Tigray, Ethiopia to exmine the response of tomato to deficit irrigation at various growth stages. A randomized complete block design with three replications was used. Combination of three irrigation regimes (100%, 50%, and 25% of full irrigation requirement) and four FAO-defined tomato growth stages (initial, developmental, mid, and late seasons) were considered to form a total of nine treatments. Data on agronomy and irrigation water were collected and analyzed statistically. The results revealed that reducing irrigation amount up to 75% during the development growth stage significantly decreased marketable yield by 66.5%. However, the highest water use efficiency (9.2 kg/m3) was achieved by reducing irrigation amount by 75% during the end-growth stage of tomatoes. Treatments with the lowest water use efficiency (3.5 kg/m3) were those receiving 75% less irrigation amount than the full requirement during the development growth stage. Reducing irrigation to less than 75% of the full requirement during tomato development stages can greatly impact marketable yield and water use efficiency. Therefore, the tomato crop is highly susceptible to water stress when receiving more than 50% of the full irrigation requirement during its developmental growth stage.